PERAN KOMPETENSI KEPEMIMPINAN GURU PAK DALAM MEMBENTUK KEPRIBADIAN PESERTA DIDIK DI SDI RIANGKEMIE - Anna Theresia Laju Golu Aran; Ignasia Yovita Kuna Koten; Margareta Ayuningsih Nerok Ola; Maria Angela Dora Kelen; Veronika Ketane Lanang; Krisantus Minggu Kwen (JIP: Jurnal Ilmu Pendidikan, 2025)
The leadership of PAK teachers can influence changes in students' personalities that are adjusted to their needs based on their abilities. A leader is said to have a good leadership style if he can influence, guide and motivate students so they can learn with the highest achievement targets. The aim of this research is to determine the impact of the leadership role of PAK teachers on the formation of students' personalities. In this research, the author applies descriptive research with qualitative research methods. The results of this research show that the personality formation of students at SDI Riangkemie has so far been carried out well through the leadership competencies of PAK teachers and supported by sekami, recollection and scout activities, in order to develop students' personality traits. However, it is still found lack of discipline, bullying and uttering dirty words between students.